ANALISIS HUBUNGAN ANTARA KEPUASAN USABILITY DAN SENTIMEN PENGGUNA: PENDEKATAN KOMBINASI SYSTEM USABILITY SCALE DAN ANALISIS SENTIMEN PADA APLIKASI SHOPEE - I Gede Pageh Widiastra; Ni Putu Vega Nirmala Kanti; Ni Made Dwi Laksmi; Gede Indrawan; I Made Agus Oka Gunawan (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The development of e-commerce in Indonesia has emphasized the importance of evaluating application quality, particularly in terms of usability and user perception. This study aims to analyze the relationship between usability and user sentiment in the Shopee application. The study employed a mixed methods approach with two types of data: primary data in the form of a SUS questionnaire from 100 Shopee user respondents, and secondary data in the form of scraped user reviews. Sentiment analysis was performed using the Naive Bayes algorithm, while the relationship between variables was evaluated using Pearson correlation. The results showed that the Shopee application obtained an average SUS score of 82, which is in the Good category. The sentiment analysis results indicated a dominance of positive sentiment compared to neutral and negative sentiment, with a classification accuracy level of 0.79. Furthermore, the Pearson correlation test obtained a coefficient value of 0.62 with a significance value (p-value) <0.05, indicating a positive and significant relationship between usability and user sentiment. These findings indicate that the better the level of application usability, the more positive user perceptions of the Shopee application. This study confirms that the SUS method and sentiment analysis can provide a more comprehensive assessment of application quality based on user experience.